Martech Collaboration untuk Pemberdayaan Desa: Meningkatkan Kinerja Bisnis Kelompok Usaha Bersama (KUBE) dan Badan Usaha Milik Desa (BUMDes) Desa Sumurjomblangbogo Pekalongan - Ahmad Syaiful Affa; Danang Satrio; Anggrainy Putri Ayuningrum; Erliana Versia Ningrum (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
KUBE and BUMDes are the primary sources of income for the village residents; however, they often face challenges in developing their businesses. These challenges include a lack of access to information about technologies that can enhance their business performance. Technology can assist KUBE and BUMDes in strengthening their businesses and improving competitiveness by increasing sales and brand image. This Community Service Program aims to provide solutions for KUBE and BUMDes to overcome these challenges through collaborative utilization of technology. Through this program, training will be conducted in the use of digital technology for Social Media Management (SMM) and Advertising Technology (AdTech). Additionally, this program will optimize collaboration between KUBE, BUMDes, the community, and the village government in product development and marketing. The outcomes of this training and mentoring include increased knowledge of KUBE and BUMDes managers about marketing technology, a 271% increase in impressions and public awareness from the most recent advertising campaign, and a 52% increase in physical visits to Tirta Arum swimming pool and the KUBE canteen compared to similar days before the advertisement was run.